Analysis of Student Creativity and Learning Interest in the Rural and Urban History Course in the Even Semester - Pujo Sukino; Sahid Hidayat (Global Education Journal, 2026)
Learning creativity can train students to be independent. This study aims to provide a comprehensive description of student creativity and learning interest in the rural and urban history course in the even semester of the 2024/2025 academic year. The research method used was descriptive with a qualitative approach. The research techniques used were direct communication, indirect communication, and documentation. The research tools included observation guides, interview guides, and learning documents. The results of the study indicate, among other things: 1) Student learning creativity in the rural and urban history course is generally quite good, as evidenced by students demonstrating creative attitudes. 2) Factors influencing student learning creativity include encouragement from the students themselves, environmental encouragement, which is the most important factor in supporting student learning creativity, and the lecturer's attitude toward student creativity. 3) Interest in the rural and urban history course is quite high because the topic is close to social reality and the course provides a fresh perspective and is not boring. This is because there are always new stories and unique tales about villages and cities from the students' hometowns.